2020
DOI: 10.4314/ahs.v20i4.57
|View full text |Cite
|
Sign up to set email alerts
|

Infertility and associated factors in three hospitals in Douala, Cameroon: a cross-sectional study

Abstract: Aim: We determined the prevalence and factors associated with couple infertility in three hospitals in Douala, Cameroon. Methods: We conducted a cross-sectional study from December 18th 2015 to March 18th 2016 in three public hospitals in Douala. Three hundred and sixty participants were studied prospectively for associated fac- tors using a multivariate logistic regression model and 4732 files were studied retrospectively for the prevalence of infertility. Statistical significance was set at p < 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
0
0
1
Order By: Relevance
“…The finding of this study is higher than that of a study performed in China in which the prevalence of infertility was 22.1% [ 33 ]. It is also higher than a similar study done in Cameroon in which the prevalence of infertility was 19.2% [ 34 ], also higher than a study done in Burkina Faso[ 35 ]. However, the finding of this study is much lower than the finding of a study done in Central Africa with a prevalence of 61% secondary infertility.…”
Section: Discussioncontrasting
confidence: 59%
“…The finding of this study is higher than that of a study performed in China in which the prevalence of infertility was 22.1% [ 33 ]. It is also higher than a similar study done in Cameroon in which the prevalence of infertility was 19.2% [ 34 ], also higher than a study done in Burkina Faso[ 35 ]. However, the finding of this study is much lower than the finding of a study done in Central Africa with a prevalence of 61% secondary infertility.…”
Section: Discussioncontrasting
confidence: 59%
“…Several studies conducted in regions such as Asia, Latin America and Africa 10 12 have identified various risk factors associated with FI. These factors include exposure to toxic substances, HIV infection, reproductive tract infections, early age at first birth, inadequate care following unsafe abortions and postpartum infections.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include exposure to toxic substances, HIV infection, reproductive tract infections, early age at first birth, inadequate care following unsafe abortions and postpartum infections. The agrarian nature of these countries often results in poor health and hygiene practices, further increasing women’s exposure to harmful chemicals 10 and subsequently raising the risk of FI. Moreover, the prevalence of HIV infection in these regions, particularly in Africa, not only impacts fertility directly but also heightens the likelihood of other reproductive tract infections.…”
Section: Discussionmentioning
confidence: 99%